2017
DOI: 10.1186/s40101-017-0131-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of waxy barley, Kirarimochi, consumption on bowel movements of late-stage elderly residents at Roken nursing home

Abstract: BackgroundIt is very important for the late-stage elderly to have the least stressful bowel movements for maintaining a good quality of life. It is generally accepted that consuming adequate dietary fiber is a promising method for the prevention and management of stressful bowel movements such as those during constipation. Therefore, we examined the effect of long-term consumption of waxy barley, which is high in dietary fiber, on the bowel movements of the late-stage elderly living at Roken nursing home (a ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 7 publications
1
5
0
1
Order By: Relevance
“…This agreed with Taniguchi et al, (2017) that found that consumption of waxy barley improved bowel movements and concluded that the consumption of dietary proper intake for 2 weeks improved defecation frequency and other symptoms of constipation. The present study disagreed with Yeun & Lee, (2015) who that there was an improvement in the elderly prevalence of functional constipation after application of the program.…”
Section: Discussionsupporting
confidence: 89%
“…This agreed with Taniguchi et al, (2017) that found that consumption of waxy barley improved bowel movements and concluded that the consumption of dietary proper intake for 2 weeks improved defecation frequency and other symptoms of constipation. The present study disagreed with Yeun & Lee, (2015) who that there was an improvement in the elderly prevalence of functional constipation after application of the program.…”
Section: Discussionsupporting
confidence: 89%
“…Of these, the Izumo City, where the survey was conducted, has a particularly advanced aging population, even more than the national average [29]. Individuals in the median age are defined as early elderly individuals in Japan, and they are relatively young among the elderly population [30]. With regard to BMI as a criterion for evaluating body shape, the target population including both men and women was of the standard body shape category (normal weight: BMI greater than or equal to 18.5 to 24.9 kg/m 2 ) when evaluated based on the WHO classification [31].…”
Section: Discussionmentioning
confidence: 99%
“…Our study was conducted in rural rather than urban areas in Japan and focused on the Ohnan area, where the super-aged society is the most advanced. According to their median age, the study participants would be considered early elderly in Japan, who are relatively young [ 39 ]. The target population, both male and female, exhibited normal weight (BMI 18.5–24.9 kg/m 2 ) when evaluated using the World Health Organization classification [ 40 ].…”
Section: Discussionmentioning
confidence: 99%